Analisis Manajemen Persediaan Bahan Makanan dengan Metode EOQ - Mariana; rohmad kafidzin (Universitas Muhammadiyah Klaten, 2026)
This study analyzes the inventory management of food ingredients in the Nutrition Unit of Kumala Siwi General Hospital Mijen Kudus by applying the Economic Order Quantity (EOQ) method. The nutrition unit is responsible for providing daily meals for inpatients, so it requires effective and efficient inventory management. The current practice shows high ordering frequency and indications of over stock for several items, especially rice, which may increase ordering and storage costs. This research aims to describe the existing inventory management policies and to evaluate the effectiveness of the EOQ method as an alternative planning tool. The study uses a descriptive quantitative design with data obtained through interviews, observation, and documentation of annual usage, ordering frequency, and inventory-related costs in 2023. EOQ calculations are performed for six types of food ingredients: rice, chicken eggs, carrots, melon, watermelon, and catfish. The results show that the implementation of EOQ reduces the frequency of ordering for all items, for example rice from 96 to 31 orders per year and watermelon from 180 to 10 orders per year. Total ordering costs decrease by 82.84%, from IDR 2,564,000 to IDR 440,000, while total usage costs decrease by 0.47%, from IDR 110,812,200 to IDR 110,295,490. These findings indicate that EOQ is effective in helping the hospital nutrition unit control inventory more efficiently without disrupting the continuity of food service for patients.